Perancangan dan Pengembangan Automatic Fish Feeder Menggunakan Aplikasi Mobile Blynk dan ESP32 - Jeffrey, Jeffrey; Elvis, Elvis; Lau, Wilsen; Tham, Vincent; Yulianto, Andik (Universitas Internasional Batam, 2024)
This research presents the design and development of an Internet of Things (IoT)-based Automatic Fish Feeder system using the Blynk platform to address common challenges in fish feeding management. The primary goal is to ensure consistent feeding schedules, minimize manual intervention, and provide remote control and monitoring capabilities. The system utilizes the ESP32 microcontroller integrated with ultrasonic sensors and servo motors to dispense feed accurately. Real-time data transmission is enabled via the Blynk Cloud, allowing users to schedule feeding times, monitor feed levels, and receive notifications when the feed stock is low. The methodology involves a multi-layer communication architecture: perception, data processing, communication, and application layers. Ultrasonic sensors calculate the remaining feed stock, while servo motors execute precise feeding commands. Users can interact through a user-friendly Blynk interface that visualizes feed levels, logs feeding history, and supports customizable schedules. The system also sends real-time alerts to ensure proactive management. The implementation successfully reduces manual feeding tasks, mitigates overfeeding risks, and enhances feed efficiency. This innovative approach supports sustainable aquaculture practices, promoting healthier fish growth for hobbyists and commercial breeders alike. Results demonstrate high reliability and user satisfaction, paving the way for future smart aquaculture solutions.